19 Things We Learned from the 2016 Election. Issue 1 (1st January 2017) - Gelman, Andrew; Azari, Julia
ABSTRACT: We can all agree that the presidential election result was a shocker. According to news reports, even the Trump campaign team was stunned to come up a winner. So now seems like a good time to go over various theories floating around in political science and political reporting and see where they stand, now that this turbulent political year has drawn to a close. In the present article, we go through several things that we as political observers and political scientists have learned from the election, and then discuss implications for the future.